Al-Quran dan Kosmologi - theo jaka prakoso (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2020)
The study of the characteristics of various kinds of energy in the universe has become the main source of human success, in achieving faith in Allah. One of them is scientific proof of the truth of the Koran against science that has been tested theoretically and empirically. This study aims to find a meeting point between the Koran and modern science regarding the interpretation of the cosmic verses regarding the origin and extinction of the universe. The information provided by the Al-Qur'an will remain secret, until the human mind can properly digest the information provided. Along with the passage of time and the development of science, Allah has gradually proven the truth of the Qur'anic information about the universe. The results of this study indicate that the Al-Quran has far preached the theory of the universe before modern science revealed it in a study.